Across America and Back : Retracing My Great-Grandparents' Remarkable Journey - Hooper, Mary Ann, 1944- (Book collections on Project MUSE., 2018)
After unearthing her great-grandparents' diaries, Mary Ann Hooper set out on a journey to retrace their 1871 trip across the United States on the newly-opened Transcontinental Railroad--via Chicago, just destroyed by the Great Fire, then across the Great Plains and Rocky Mountains to the Golden City of San Francisco. Filled with rich details of time, place, and culture, Mary Ann's thoughtful and compelling narrative is both a re-creation of a family journey and a thoughtful account of how the American West has changed over the last 150 years. Using the common thread of the same train trip across the American landscape, she weaves together the two stories--her great grandparents, Charles and Fannie Crosby's leisurely Victorian tourist trip described in both their diaries--and her own trip. Mary Ann's adventurous and determined voice fills the pages with entertaining encounters on the train, escapades on her folding bike, and her reflections on her birth country and her own life story. During her journey, she discovers the stories of her 1950s childhood reflect a "Wild West" at odds with the West her great-grandparents record in their diaries, leading her to uncover more of the real and meatier history of the American West--going through conquest, rapid settlement, and economic development. As Mary Ann fulfills her quest to understand better why glorified myths were created to describe the Wild West of her childhood, and reflects on the pitfalls of what "progress" is doing to the environment, she is left with a much bigger question: Can we transform our way of doing things quickly enough to stop our much-loved West becoming an uninhabitable desert?